Peri-Implantation Hormonal Milieu: Elucidating Mechanisms of Adverse Neurodevelopmental Outcomes. (June 2016) - Mainigi, Monica; Rosenzweig, Jason M.; Lei, Jun; Mensah, Virginia; Thomaier, Lauren; Talbot, C. Conover; Olalere, Devvora; Ord, Teri; Rozzah, Rayyan; Johnston, Michael V.; Burd, Irina
While live births resulting from assisted reproductive technology (ART) exceed 1% of total births annually, the effect of ART on fetal development is not well understood. Data have demonstrated that IVF leads to alterations in DNA methylation and gene expression in the placenta that may have long-term effects on health and disease. Studies have linked adverse neurodevelopmental outcomes to ART, although human studies are inconclusive. In order to isolate the peri-implantation environment and its effects on brain development, we utilized a mouse model with and without superovulation and examined the effect of adult behavior as well as adult cortical neuronal density. Adult offspring of superovulated dams showed increased anxiety-like behavior compared to offspring of naturally mated dams ( P < .05). There was no difference in memory and learning tests between the 2 groups. The adult brains from offspring of superovulated recipients had fewer neurons per field compared to naturally mated control offspring ( P < .05). In order to examine potential pathways leading to these changes, we measured messenger RNA and microRNA (miRNA) expression in fetal brains at E18.5. Microarray analysis found that miRNAs miR-122, miR-144, and miR-211, involved in regulation of neuronal migration and differentiation, were downregulated in brains of offspring exposed to a superovulated environment( P < .05). There was also altered expression of genes involved in neuronal development. These results suggest that the peri-implantation environment can affect neurodevelopment and can lead to behavioral changes in adulthood. Human studies with long-term follow-up of children from ART are necessary to further investigate the influence of ART on the offspring.